Farm risks, livelihood asset allocation, and adaptation practices in response to climate change: A cross-country analysis - Sargani, Ghulam Raza; Shen, Yun; Liu, Yan; Joyo, Mumtaz Ali; Liu, Jing; Jiang, Yuansheng; Zhang, Huaquan (Frontiers in Environmental Science, 2023)
The study's purpose is to examine the impact of farm risk on livelihood asset allocation and adaptation practices to cope with climate change. An interview-based study with farmers is conducted in China and Pakistan and employs probit regression models to analyze the data. The results confirm that Pakistani growers' natural and policy risks, whereas technology and information risks in China, are the main livelihood risks to farm production. Farmers' natural, physical, social, and human assets in China, while Pakistan's financial, physical, and social assets can protect their livelihoods from farm risks. In Pakistan, physical, social, and economic assets and physical, human, and social assets show contradictory effects in China. Although farmers in China adopted agrotechnical support, off-farm production, crop variety adjustment, and agricultural engineering, Pakistan growers adopted agricultural finance, fertilizer/water management, and adjustment of crop varieties to deal with risks. Moreover, social, natural, human, and physical assets revealed significant and positive impacts on Pakistani growers; physical and financial assets positively affect Chinese growers' attitudes. Despite Chinese growers' human, social, and natural assets, Pakistani farmers' financial and natural assets show comparatively weak effects to adapt and deal with climatic risks. Furthermore, this study recommends agricultural policy measures to cope with climate awareness and adaptive attitudes, and potential practices can be induced in both studied areas.